2019
DOI: 10.1016/j.nicl.2018.11.004
|View full text |Cite
|
Sign up to set email alerts
|

FDG-PET hypometabolism is more sensitive than MRI atrophy in Parkinson's disease: A whole-brain multimodal imaging meta-analysis

Abstract: Recently, revised diagnostic criteria for Parkinson's disease (PD) were introduced (Postuma et al., 2015). Yet, except for well-established dopaminergic imaging, validated imaging biomarkers for PD are still missing, though they could improve diagnostic accuracy.We conducted systematic meta-analyses to identify PD-specific markers in whole-brain structural magnetic resonance imaging (MRI), [18F]-fluorodeoxyglucose-positron emission tomography (FDG-PET) and diffusion tensor imaging (DTI) studies. Overall, 74 st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
55
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(78 citation statements)
references
References 68 publications
7
55
5
Order By: Relevance
“…A previous cross-sectional study investigating both metabolism and atrophy in cognitively impaired and cognitively preserved pwPD concluded that hypometabolism may precede GM volume loss and may be progressively replaced by atrophy during cognitive worsening (46). The greater ability of FDG-PET to reveal significant PD-related alterations compared to MRI-VBM is in line with this hypothesis (45). Parietal GM atrophy may be a feature that is mainly associated with late stage of PD, when cognitive impairment is already established.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…A previous cross-sectional study investigating both metabolism and atrophy in cognitively impaired and cognitively preserved pwPD concluded that hypometabolism may precede GM volume loss and may be progressively replaced by atrophy during cognitive worsening (46). The greater ability of FDG-PET to reveal significant PD-related alterations compared to MRI-VBM is in line with this hypothesis (45). Parietal GM atrophy may be a feature that is mainly associated with late stage of PD, when cognitive impairment is already established.…”
Section: Discussionmentioning
confidence: 63%
“…The presence of parietal hypoperfusion in absence of parietal GM atrophy and its association with the TMT A score are the main findings that were observed. Although the majority of PD studies that have previously detected parietal hypoperfusion or hypometabolism included cognitively impaired cohort of subjects (11,15,(43)(44)(45), few works reported alterations in SPL (14,16) and IPL (14,46) even in absence of frank cognitive impairment. Cortical hypometabolism was detected in the posterior parietal cortex of non-demented PD patients with both phosphorus-31 magnetic resonance spectroscopy and FDG-PET (14).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, to investigate disease-specificity of the results, we ran subtraction analyses comparing the present results with the findings of our recently published meta-analysis on Parkinson's disease (For further information please refer to Albrecht et al, 2018). We used the results at p < 0.001 uncorrected from the present analysis and the white and gray matter MRI cohort of the Parkinson's disease meta-analysis (cohort with Parkinson's disease only).…”
Section: Methodsmentioning
confidence: 99%
“…To investigate disease-specificity we run subtraction analyses to compare PSP with related diseases, i.e. Parkinson's disease (Albrecht et al, 2018). We hypothesized atrophy in PSP of white matter in the midbrain and gray matter in the midbrain, thalamus, and insulae (Shao et al, 2014; Shi et al, 2013; Yu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Preserved glucose metabolism in the basal ganglia may differentiate PD from MSA and PSP, where a corresponding glucose hypometabolism is typically seen in the latter (259). A meta-analysis found decreased glucose metabolism in the bilateral inferior parietal cortex and left caudate nucleus in PD, which was linked to cognitive deficits and motor symptoms, respectively (261). In MSA, glucose hypometabolism may be observed in the putamen and brainstem, with or without hypometabolism in the cerebellum compared to PD and controls (259,262).…”
Section: Pet Imaging Of Glucose Metabolism In Parkinsonian Disorders mentioning
confidence: 99%